Development of Organic Based Rice Farming on Ecosystem and Culture of Subak In Bali - Cening Kardi; Putu Fajar Kartika Lestari; Ni Putu Sukanteri (Syntax Idea)
Green Revolution technology changed the behavior of farmers from low-input traditional rice farming to high-input modern rice farming, which had implications on the use of excessively synthetic fertilizers and pesticides, degradation of rice fields, and the extinction of some local paddy varieties which had high-quality rice. This is contrary to the global issue of food security, which requires high-quality rice products with safety assurance of the absence of pesticide residues and other synthetic chemicals, before entering the international market. The solution on the fourth is back to nature by cultivating environmentally friendly technology through organic-based Cicih Gondrong rice farming. This study aims to facilitate and educate rice farming using the local resource (compost from cattle manure, grass, and rest crop and Cicih Gondrong rice), and reduction of external input. Further rice intensification technology through an approach of eco-farming and subak culture wisdom to improve the efficiency of input allocation toward more profitable and sustainable rice farming. The methods of survey and demonstration plots are used to arrange production functions and efficiency tests on Cicih Gondrong rice farming. The demonstration plot of organic-based rice farming using specific techniques of cultivation. This blended method is expected can produce a Model development of organic-based Cicih Gondrong rice farming on the ecosystem and culture of subak. The significance: (1) to enrich the Agribusiness Management with eco-cultural based rice farming (2) the improvement and conservation local rice farming to increase productivity and profitability and sustainability of rice farming in subak and strengthen Bali's local secure food.